La Contribution de L’audit Interne dans L’amélioration de L’efficacité du Contrôle Interne dans L’entreprise Algérienne: le Cas d’ATM Mobilis - Boudia, Mounya; Debbi, Ali (جامعة محمد خيضر بسكرة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
Internal auditor ensures the proper functioning of internal control and controls risks likely to generate malfunctions. The purpose of this article is to highlight the role of the internal auditor in the evaluation of internal control in Algerian companies. For that, we conducted a case study within the ATM Mobilis telephone operator. The result of our research confirms the contribution of internal audit in controlling the risks and in improving the effectiveness of internal control set up by management.
Keywords: الشركات الجزائرية -- قطاع الاتصالات -- الرقابة الداخلية -- الإدارة الاستراتيجية